Answer:
See explanation
Step-by-step explanation:
Solution:-
- We will use the basic formulas for calculating the volumes of two solid bodies.
- The volume of a cylinder ( V_l ) is represented by:
![V_c = \pi *r^2*h](https://tex.z-dn.net/?f=V_c%20%3D%20%5Cpi%20%2Ar%5E2%2Ah)
- Similarly, the volume of cone ( V_c ) is represented by:
![V_c = \frac{1}{3}*\pi *r^2 * h](https://tex.z-dn.net/?f=V_c%20%3D%20%5Cfrac%7B1%7D%7B3%7D%2A%5Cpi%20%2Ar%5E2%20%2A%20h)
Where,
r : The radius of cylinder / radius of circular base of the cone
h : The height of the cylinder / cone
- We will investigate the correlation between the volume of each of the two bodies wit the radius ( r ). We will assume that the height of cylinder/cone as a constant.
- We will represent a proportionality of Volume ( V ) with respect to ( r ):
![V = C*r^2](https://tex.z-dn.net/?f=V%20%3D%20C%2Ar%5E2)
Where,
C: The constant of proportionality
- Hence the proportional relation is expressed as:
V∝ r^2
- The volume ( V ) is proportional to the square of the radius. Now we will see the effect of multiplying the radius ( r ) with a positive number ( a ) on the volume of either of the two bodies:
![V = C*(a*r)^2\\\\V = C*a^2*r^2](https://tex.z-dn.net/?f=V%20%3D%20C%2A%28a%2Ar%29%5E2%5C%5C%5C%5CV%20%3D%20C%2Aa%5E2%2Ar%5E2)
- Hence, we see a general rule frm above relation that multiplying the result by square of the multiple ( a^2 ) will give us the equivalent result as multiplying a multiple ( a ) with radius ( r ).
- Hence, the relations for each of the two bodies becomes:
![V = (\frac{1}{3} \pi *r^2*h)*a^2](https://tex.z-dn.net/?f=V%20%3D%20%28%5Cfrac%7B1%7D%7B3%7D%20%5Cpi%20%2Ar%5E2%2Ah%29%2Aa%5E2)
&
![V = ( \pi *r^2*h)*a^2](https://tex.z-dn.net/?f=V%20%3D%20%28%20%5Cpi%20%2Ar%5E2%2Ah%29%2Aa%5E2)
60% if there are only 10 white and black balls
Answer:
1)y=-3+5x
2)y=5/2-1/2x
Step-by-step explanation:
for both equations
1) get your y by it self (subtract -5x and your new equation is now -y=-5x+3)
2)(reminder y can't be negative if it is negative) then you divide by -1 of both sides
3) your equation should now be y=5x-3